Growth and electrical properties of LuFe2O4 crystal. - Kwan, Philip. (2009)
Materials with resistive switching capabilities upon external stimulus are drawing more attention due to its rich physics as well as great potential in developing electronic devices. One of its potential applications is in developing new memory schemes based on a change of electrical properties upon external stimulus. LuFe2O4 has emerged as one of the candidates to be used in this memory schemes.